2011
DOI: 10.1038/bjc.2011.441
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor genotypes predict response to endocrine treatment in breast cancer patients

Abstract: Background:The androgen receptor (AR) is frequently expressed in breast cancers. The AR genotype may affect disease-free survival and response to endocrine therapy.Methods:In all, 634 women undergoing breast cancer surgery between 2002 and 2008 were followed until 30 June 2010. Six haplotype-tagging single-nucleotide polymorphisms in the AR, and the resulting AR diplotypes, were examined in relation to breast cancer patient characteristics, tumour characteristics, disease-free survival, and response to endocri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 43 publications
1
31
0
1
Order By: Relevance
“…A recent report from a subset of the current patient cohort, showed that certain androgen receptor (AR) genotypes were associated with significantly larger breast size, but not with increased WHR. These AR genotypes were also significantly associated with shorter disease-free survival (47 (9). In Enger's study, only 73% of the tumors were ER-positive compared to over 85% in Lund.…”
Section: Discussionmentioning
confidence: 87%
“…A recent report from a subset of the current patient cohort, showed that certain androgen receptor (AR) genotypes were associated with significantly larger breast size, but not with increased WHR. These AR genotypes were also significantly associated with shorter disease-free survival (47 (9). In Enger's study, only 73% of the tumors were ER-positive compared to over 85% in Lund.…”
Section: Discussionmentioning
confidence: 87%
“…Other preclinical data showed that AR blocks ERstimulated growth in breast cancer cells (6) and that overexpression of AR decreased ER transcriptional activity (48). Whether different AR genotypes are reflected in AR expression in breast tumors is unknown, but we have recently reported on AR genotypes predicting response to TAM treatment (49). The treatment predictive value of tumor-specific AR expression has been addressed in endocrine-treated cohorts, demonstrating high AR expression to be a predictive factor for response to endocrine treatment (10).…”
Section: Discussionmentioning
confidence: 98%
“…In a previous study, we reported a treatment predictive value of AR genotyping for adjuvant TAM, but not for AIs (9). In this study, we hypothesized that the prognostic value of tumor AR expression may depend on ER status and have predictive value for endocrine treatment response.…”
Section: Introductionmentioning
confidence: 90%
“…Information on breast cancer events and date of death was obtained from patient charts, the regional tumor registry, and the population registry. Genotyping of the six haplotypes tagging single nucleotide polymorphisms in the AR (rs1337080, rs17302090, rs6152, rs7061037, rs5031002, and rs5964607) was done as previously described (9).…”
Section: Introductionmentioning
confidence: 99%